2003
DOI: 10.1109/tbme.2003.812222
|View full text |Cite
|
Sign up to set email alerts
|

Radio-wave exposure of the human head: analytical study based on a versatile eccentric spheres model including a brain core and a pair of eyeballs

Abstract: A versatile eccentric-spheres model of the human head is used in this paper to investigate radio-wave absorption. Numerical results, obtained by use of an exact analytical solution, are presented for the total, percentage, and gram-specific absorption. Interest is mainly in the brain and in the eyes of an adult or an infant head. Our model comprises a host sphere and several spherical inclusions, all concentrically stratified with respect to their own center. Any number of inclusions and any number of concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…Moneda et al [11] investigate radio frequency wave absorption on a human head model. Hirata et al [7] calculate the SAR for the interaction of the human eye with electromagnetic waves in the Industrial, Scientific, and Medical (ISM) frequency bands.…”
Section: Related Workmentioning
confidence: 99%
“…Moneda et al [11] investigate radio frequency wave absorption on a human head model. Hirata et al [7] calculate the SAR for the interaction of the human eye with electromagnetic waves in the Industrial, Scientific, and Medical (ISM) frequency bands.…”
Section: Related Workmentioning
confidence: 99%
“…Let the subscripts " [1]" and " [2]" denote the outer and inner spheres, respectively. With the wave vector (complex number) in this region denoted by k and the position vector with respect to the center of the sphere denoted by r, the scalar potential φ(r) representing the general solution to the scalar Helmholtz equation can be found as follows [3]:…”
Section: Basic Expression Of Field and Calculation Methods For Absorbementioning
confidence: 99%
“…However, such models are too simple in shape, and the verification is not sufficiently reliable. On the other hand, for models involving an arbitrary number of eccentric or separate nonoverlapping spheres, Moneda and colleagues [2] and Gumerov and Duraiswami [3] have shown that exact solutions for the time-harmonic electromagnetic field can be obtained by analytic methods using an infinite series expansion applied to the Helmholtz field. Using such calculation results for the aforesaid verification problem allows considerable improvement of reliability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of ρ i for the different tissues of the model are taken from [10] and are given in Table 2.…”
Section: Numerical Methods and Modelingmentioning
confidence: 99%